Prevalence of causative bacteria on cell phones of patients with chronic suppurative otitis media: a descriptive cross-sectional study - Ekanayake, Lakshantha Sapumal Bandara; Uganathan, Ananthakirushnan; Abeykoon , Muditha (International Surgery Journal, 2024)
Background: The aim of this study is to identify the prevalence of causative bacteria on the cell phones of patients with chronic suppurative otitis media (CSOM). Methods: Fifty clinic patients were randomly selected according to the eligibility criteria. Ear swab samples and swabs from the ear-piece area of their cell phones were collected for laboratory investigation. Additionally, 20 controls were recruited for comparison. Results: Among the 50 subjects, 60% were Females, and the highest prevalence was observed in the 36-45 age group. Ear swab cultures showed bacterial growth in 32 samples (64%), with Pseudomonas spp. (24%) being the most prevalent, followed by coagulase-negative Staphylococcus spp. (14%) and Staphylococcus aureus (14%). Only 11 out of 50 phone swabs (22%) showed bacterial growth, predominantly coagulase-negative Staphylococcus spp. (18%). In three cases, the same non-pathogenic bacteria (coagulase-negative Staphylococcus spp.) were found in both ear and phone samples. Among the controls, 55% were female, and the highest prevalence was in the 26-35 age group. Four ear swab samples (20%) from the controls grew coagulase-negative Staphylococcus spp., but phone samples showed inconsistent laboratory results due to technical issues. Conclusions: Based on the findings, there is no significant prevalence of CSOM causative bacteria on the cell phones of patients. However, limitations, including sample size and the inability to establish a causal relationship, should be considered. Larger studies exploring multiple environmental reservoirs may better clarify potential transmission routes for CSOM pathogens.